Keterancaman Leksikon dan Kearifan Lokal dalam Perkakas Pertanian Tradisional Jawa - Rangga Asmara; Khamimah Khamimah (Universitas Tidar, 2019)
This research is aimed to (1) identify the noun phrases of the endangered traditional farming tools, (2) explain the values of local wisdom which are reflected in traditional farming tools in Java, and (3) explain the efforts that can be done to conserve the noun phrases of the endangered traditional farming tools in Java. The research data consist of many kinds of noun phrases of traditional farming tools in Java in every speech act by the traditional farmer from Javanese ethnic that is gotten from the interview and observation in Magelang district and Sleman district. The verbal data were collected with an observation method. The result of this research showed that 46.3% respondent knew any number of noun phrases in the questionnaire. In reverse, 53.7% respondent did not know any number of noun phrases in the questionnaire. The local wisdom found in this research were the meanings from the noun phrases of traditional farming tools in Java. The meanings have certain values of local wisdom with the beneficial aims for human life. Furthermore, the efforts that can be done to conserve traditional farming tools in Java are (1) exposing this research in a form of article and journal about traditional farming tools, (2) socializing traditional farming tools in Java through explaining and showing pictures to respondents who have filled the questionnaire. This socialisation is done by giving pictures of traditional farming tools in Java and explaining about the function.